The Search for sunken treasure. - Stilton, Geronimo (New York: Scholastic, 2006)
Holey Cheese, what an adventure! I was off to the Ratlapagos Islands on a quest for buried treasure. But oh, how I hate traveling! But oh, how I hate traveling! Being on a ship in the middle of the sea wasn't my idea of a fabumouse time. And I was beginning to suspect that Thea, Trap, and I weren't the only ones searching for he treasure....
Keywords: Treasure hunts. -- Adventure